Podcasts as a Communication Media in Increasing Knowledge of the Millennial Generation - Dolly Syaitiawan; Sapta Sari; Anis Endang (Penerbit Jurnal Indonesia, 2023)
According to the background about the problem in this research, the purpose of this research is to improve the knowledge which still unknown about politics, economics, new knowledge also speaking style which obtained from the guest the podcast host. This research uses qualitative research and data are collected by using observation, interview, documentation. The theory which used in this research is Notoatmodjo (2012). The result of this research is to find out about information, education, and entertainment. The benefit obtained from watching the Deddy Corbuizer podcast is to obtain information about political history, economics, new knowledge, and how to be good and correct in speaking technique also to make the communication are delivered with a relaxed style and not too difficult and avoid ambiguity.